2017
DOI: 10.1016/j.reprotox.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Preconception exposure to dietary levels of genistein affects female reproductive outcomes

Abstract: Genistein is a phytoestrogen found in soy and soy-based products. Previously, we found that genistein adversely affected estradiol levels and follicle growth in vitro. Proper hormone production and follicle growth are key regulators of normal fertility. Therefore, we hypothesized that genistein adversely affects female fertility and pregnancy outcomes. To test this hypothesis, we dosed sexually mature female CD-1 mice (35 days) with 0, 300, 500, or 1000 ppm genistein for 30, 60, 150, and 240 days. At the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Female mice were killed at the diestrus stage of the estrous cycle (when estradiol levels are low) to minimize the variability in hormone levels during the estrous cycle (Patel et al. ). For both male and female mice, the chest cavity was opened and blood was collected from the right ventricle of the heart for immediate serum separation, which was then stored at −20°C prior to serum estradiol level measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Female mice were killed at the diestrus stage of the estrous cycle (when estradiol levels are low) to minimize the variability in hormone levels during the estrous cycle (Patel et al. ). For both male and female mice, the chest cavity was opened and blood was collected from the right ventricle of the heart for immediate serum separation, which was then stored at −20°C prior to serum estradiol level measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Mice treated with 500 ppm genistein for 60 days had decreased litter size and increased average pup weight compared to control mice. Additionally, mice treated with 300 ppm genistein for 150 days had an increased risk of prolonged parturition compared to control mice [7]. Interestingly, Patel et al [7] showed that genistein exposure also had a non-linear effect on fertility in mice, with the 300 ppm genistein group showing reduced fertility at 240 days compared to control mice, but the 500 and 1000 ppm genistein groups showing higher fertility at 240 days compared to control mice.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mice treated with 300 ppm genistein for 150 days had an increased risk of prolonged parturition compared to control mice [7]. Interestingly, Patel et al [7] showed that genistein exposure also had a non-linear effect on fertility in mice, with the 300 ppm genistein group showing reduced fertility at 240 days compared to control mice, but the 500 and 1000 ppm genistein groups showing higher fertility at 240 days compared to control mice. Genistein exposure did not affect levels of estradiol or progesterone in Patel et al [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isoflavonoid genistein is an ED whose uterine or neonatal exposure is correlated to induction of several effects in female mice as reproductive disorders (Drummond and Fuller 2010;Patisaul 2009), increase in ano-genital distance (masculinization), accelerated puberty and irregular estrous cycles (Jefferson et al 2005). Preconception exposure to genistein also affects gestation time, parturition time, litter size, pup weight, and pup mortality in mice (Patel et al 2017). According to Whirledge et al (2015), genistein can modulate the ER activity, leading to the development of various uterine pathologies in humans.…”
Section: Epigenetic Effectsmentioning
confidence: 99%